Evaluation of Applications of Intrauterine Progesterone Versus Oral Progesterone in the Treatment of Dysfunctional Uterine Bleeding - Muhammad Jamil Johar, Nasreen Akhtar, Sara Akram, Farzana Sabir, Farzana Burki, Khunsa Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) is a common gynecological problem that affects the women of all ages. It is defined as any irregular or excessive bleeding from the uterus that is not related to the woman’s normal menstrual cycle. It can be caused by a many of underlying factors such as hormonal imbalance, fibroids, polyps or endometriosis. Study design: It is a randomized controlled study conducted at Divisional Headquarters Teaching Hospital Mirpur Azad Kashmir and Lady Willingdon Hospital Lahore for the duration of six months from June 2022 to November 2022. Material and Methods: The study was carried out for two groups. Intrauterine group included the patients that received intrauterine dose of progesterone and oral group patients had progesterone orally. The study was approved by the review board committee of the hospital. The use of pads for both groups was studied and it was found that oral group used the most pads 18.7 and 12.9 before and after the study respectively. Results: Duration of bleeding was examined. The patients in intrauterine group stated about bleeding for 7.8 days before the study and 5.9 days after the study. In case of oral group participants, they bled for 8.9 days before the study and 6.7 days after the study. Standard deviation and p value was calculated and results were statistically significant. Conclusion: The investigation of oral and intrauterine progesterone for patients suffering from dysfunctional uterine bleeding was studied and it was found that the rate of bleeding was more in case of oral group. Keywords: Intrauterine progesterone and oral progesterone.